Short-Term Prediction of Preeclampsia in Chinese Women Using the Soluble fms-Like Tyrosine Kinase 1/Placental Growth Factor Ratio: A Sub-Analysis of the PROGNOSIS Asia Study - Gao, Jinsong; Huang, Xianghua; Di, Wen; Dong, Xiaojing; Gou, Wenli; Shi, Hong; Wang, Zilian; Dietl, Angela; Grill, Sonja; Hund, Martin (Frontiers in Cardiovascular Medicine, 2021)
The diagnosis of preeclampsia in China currently relies on limited clinical signs and unspecific laboratory findings. These are inadequate predictors of preeclampsia development, limiting early diagnosis and appropriate management. Previously, the Prediction of Short-Term Outcome in Pregnant Women with Suspected Preeclampsia Study (PROGNOSIS) and PROGNOSIS Asia demonstrated that a soluble fms-like tyrosine kinase 1 (sFlt-1)/placental growth factor (PlGF) ratio of ≤38 can be used to rule out preeclampsia within 1 week, with negative predictive values of 99.3 and 98.6%, respectively. This is an exploratory sub-analysis of the Chinese cohort (n = 225) of the PROGNOSIS Asia study. The primary objectives were to assess the predictive performance of using the sFlt-1/PlGF ratio to rule out preeclampsia within 1 week and to rule in preeclampsia within 4 weeks. The sFlt-1/PlGF ratio was also examined for short-term prediction of fetal adverse outcomes, maternal adverse outcomes, and time to delivery. The overall prevalence of preeclampsia was 17.3%. With the use of an sFlt-1/PlGF ratio of ≤38, the negative predictive value for ruling out preeclampsia within 1 week was 97.3% [95% confidence interval (CI), 93.8–99.1], with a sensitivity of 64.3% and specificity of 85.3%. With the use of an sFlt-1/PlGF ratio of >38, the positive predictive value for ruling in preeclampsia within 4 weeks was 35.0% (95% CI, 20.6–51.7), with a sensitivity of 50.0% and specificity of 86.8%. In the analyses of the sFlt-1/PlGF ratio and fetal adverse outcomes, the area under the receiver operating characteristic curve was 92.8% (95% CI, 83.5–98.7) for ruling out fetal adverse outcomes within 1 week and 79.9% (95% CI, 68.1–90.3) for ruling in fetal adverse outcomes within 4 weeks. An sFlt-1/PlGF ratio of >38 increased the likelihood of imminent delivery 3.3-fold compared with a ratio of ≤38 [hazard ratio, 3.3 (95% CI, 2.1–5.1)]. This sub-analysis confirms the high predictive performance of the sFlt-1/PlGF ratio cutoff of 38 for short-term prediction of preeclampsia in Chinese women, which may help prevent unnecessary hospitalization of women with low risk of developing preeclampsia.